2020
DOI: 10.21608/ejchem.2020.27264.2568
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for the preparation of conductive methyl cellulose-silver nanoparticles-polyaniline-nanocomposite

Abstract: A NOvel green method for the synthesis of conductive nanocomposite-using silver nitrate, methyl cellulose (MC), glycerol, and aniline-was adopted. Here, silver nitrate was used as a precursor, methyl cellulose as both reducing and capping agent, glycerol as a co-reducing and ductility agent and water as solvent. While silver nitrate oxidizes aniline to polyaniline, it is reduced to silver nanoparticles. Doing so, both conductive polyaniline and conductive silver nanoparticle were in-situ synthesized via the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…Moreover, it is observed that the formed nanoparticles are homogeneously dispersed and distributed throughout the film surface, which is further stabilized by the polymer (Figure 6c). [26] Even though, there has been significant nanoparticle aggregation, no direct fusion has been observed due to the presence of capping agents. Conversely, Figure 6d represents the dispersion of AgNPs formed by the addition of AgNO 3 into PVA/MC cross‐linked blend, which were slightly larger size than AgNPs present in the uncross‐linked blend.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it is observed that the formed nanoparticles are homogeneously dispersed and distributed throughout the film surface, which is further stabilized by the polymer (Figure 6c). [26] Even though, there has been significant nanoparticle aggregation, no direct fusion has been observed due to the presence of capping agents. Conversely, Figure 6d represents the dispersion of AgNPs formed by the addition of AgNO 3 into PVA/MC cross‐linked blend, which were slightly larger size than AgNPs present in the uncross‐linked blend.…”
Section: Resultsmentioning
confidence: 99%
“…(14) 2.6.3 Synthesis the colloidal solution using Xanthan gum A beaker containing 150 ml of DI water at laboratory temperature, sprinkle 0.8042 g of Xanthan gum (dynamic viscosity of a 2% solution 4000 cl) on it and stir vigorously to ensure that the material is dispersed in the solvent, and a clear colloidal solution is formed, and 0.02 g of the nanomaterial is dispersed In a beaker containing 50 ml of deionized water for 60 minutes, then add the colloidal substance of DI water and stir the solution for 30 minutes at room temperature, and finally the formation of a silver colloidal solution of methyl-dopa pharmaceutical nanocomposites can be observed. (15) 2.6.4 Synthesis a medical mask containing the nanocolloidal solution From the concentrated solution of methyldopa nanocompounds, three different concentrations (100, 50, and 150) ppm were prepared. In the previously prepared solutions, small previously prepared pieces of masks measuring (55) cm in size began to be soaked for a period of (5-7) hours.…”
Section: Preparing Some Nano Composites Decorated With Some Pharmaceu...mentioning
confidence: 99%
“…By the same group, many nanoparticles were fabricated in the presence of chitin, ascorbic acid, sodium alginate, and pectin [37][38][39]. Silver nanoparticles or silver blended zinc oxide have been incorporated into the fabric, especially cotton, with different methods in order to reduce the proliferation of bacteria and germs [40][41][42][43]. Several studies have reported that the number and position of surface plasmon resonance analysis peaks differ according to the shape and size of silver nanoparticles, as these particles tend to show different physical and biological properties that depend on their size and shape [44][45][46].…”
Section: Introductionmentioning
confidence: 99%